TANGGUNG JAWAB AHLI WARIS TERHADAP DEBITUR YANG MENINGGAL DAN DINYATAKAN PAILIT DITINJAU DARI UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Amanda Atika Yuliani Puteri (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT One of the criteria for implementing agreements made by creditors and debtors is guarantees because this guarantee can give confidence to creditors that the debtor will repay the loan. But in general, what happens in the business world, debts and receivables between creditors and debtors do not always run smoothly as promised. The debtor who should have fulfilled the obligation to pay his debt or performance, because of something unable to fulfill the obligations or achievements that should have been received by the creditor from the debtor, then the right step to solve it is through bankruptcy legal instrument, containing a rule that can regulate the relationship of the parties. and also regarding rights and obligations. This type of research is normative juridical research, library research with the problem approach used in the writing of this thesis is a statute approach.The results showed that the responsibility of the heirs to the debtor who died and was declared bankrupt, the heirs could choose one of 3 (three) attitudes, namely: accept as a whole, be inclusive of the heir's debt, accept on condition, the inheritance is received in detail, while the debt is the heir will be paid based on the property received by the heir, and refuse the heir does not want to know about the settlement of the inheritance. Protection of property belonging to an heir of a debtor who has died and is declared bankrupt, namely the bankrupt debtor who still has control and management rights over several items as stipulated in article 22 in conjunction with article 21 of the Bankruptcy and Suspension of Debt Payment Obligations, which excludes or separates the debtor's personal assets that are not related to the bankruptcy.Keywords: Bankruptcy, Inheritance and Legal Protection